Singularly perturbed linear boundary-value problems with pulse effects and the regular reduced problem - Karandjulov, L.I. (Український математичний журнал, 1995)
A singularly perturbed linear boundary-value problem with pulse effect is considered. By using pseudo-inverse matrices, we construct an asymptotic solution with a single boundary layer. Розглядається сингулярно збурена лінійна крайова задача з імпульсною дією. За допомогою псевдообернених матриць побудовано асимптотичний розв'язок з одним примежовим шаром.